BUROCRACIA DE MÉDIO ESCALÃO E FINANCIAMENTO DO ESPORTE UNIVERSITÁRIO (Fiep Bulletin - online, 2024)
Introduction: The Middle Level Bureaucracy (MLB) operates in the implementation of public policy and has endogenous action in the State. With technical-managerial and technical-political roles, it is relevant in university sports (US), which lacks robust rules and funding. Objective: To verify from a relational perspective the technical-managerial and technical-political actions that BME carried out to guarantee the financing of university sports at the Federal University of Mato Grosso (UFMT). Methods: Qualitative research, with data collection through via semi-structured interviews with four EU BMEs from UFMT and documents. Data analysis was performed using the content analysis technique. Results: The documents did not reveal the existence of financing for university sports. BME managed, via a relational perspective, to adopt a specific budget with linear growth, however, due to contingencies followed by government fiscal austerity and the pandemic event, there was a drastic reduction in financing. Conclusion: MLB has become an essential element for university sports at UFMT, exercising its technical-managerial and technical-political roles, even though it has not been able to avoid the drastic reduction in funding caused by internal and external changes and the absence of robust rules.